Optimal Capital Structure of PT Garuda Indonesia Tbk. - Abdillah, Muhammad Bisma; Kitri, Mandra Lazuardi (Journal of Business and Management, 2020)
Abstract. PT Garuda Indonesia Tbk. is a well-known Indonesian national airline and has several subsidiaries such as PT Aerowisata, PT Sabre Travel Network Indonesia, PT Garuda Maintenance Facility Aero Asia, PT Citilink Indonesia, PT Aero Systems Indonesia, PT Gapura Angkasa and Garuda Indonesia Holiday France. As of April 2020, most of the airline companies has lost many passengers due to the traveling restriction from the government to avoid disease transmission of Coronavirus pandemic. Since then, PT Garuda Indonesia Tbk. should stop some flights to a certain domestic areas and foreign countries and also reduce the amount of passenger up to 50% and do a medical check for all passengers in every flight. Even more, in June 3, 2020, PT Garuda Indonesia is required to pay a maturing debt of USD 500 million to global sukuk limited and government plans to provide a loan of IDR 8.5 trillion or as much as USD 600 million at an exchange rate of IDR 14,000 as of assumed exchange rate in 2020. Considering the recent condition of restriction of flights, reduced amount of passenger, and an increased cost of medical check, the author do a research into this company to determine what company action will PT Garuda Indonesia Tbk. should take. In order to decide whether the company accept the loan or not, the author analyses the current weighted average cost of capital of PT Garuda Indonesia Tbk. and searches the optimal capital structure so as to compare the debt and equity proportion of the current and optimal condition of them. Also, the author find the best alternative financing strategy the company had to take. PT Garuda Indonesia Tbk. currently has 76% of debt and 24% of equity, where the cost of capital is 9.06% and through WACC analysis, the authors have found that the optimal capital structure that PT Garuda Indonesia Tbk. must have to finance the maturing debt so that the value of the company at maximum, and should consist of USD 1,583,506,477 of debt and USD 1,404,241,592 of equity, which is 53% of debt and 47% of equity.Keywords: Weighted Average Cost of Capital, Optimal Capital Structure, PT Garuda Indonesia Tbk.